Controle aprimorado para console de jogos eletrônicos - Cavali, Thiago dos Santos (2015)
With the electronic games evolution, mainly the fighting genre, in many different consoles, it’s visible an increase on the difficulty of the gameplay, which can provide a less pleasurable game for the player. In this context, the development of tools which could enhance the fighting games gameplay is valid. This project aims to develop an enhanced control with arcade format that can with a single button perform a sequence of blows (combos) which, many times, are hard to make normally. It’s based on the integration of a PlayStation® PS3TM joystick with a board which contains a microcontroller AT89S52 and a EEPROM memory AT24C512, in addition to analogic keys with digital command integrated circuits CD4066. The combos previously recorded (by software or by hardware) on EEPROM memory are interpreted by microcontroller that triggers the proper keys, performing the combo. This project results in an attractive joystick for the players, which improves the fighting games gameplay.